Photogrammetric measurement of 3D freeform millimetre-sized objects with micro features: an experimental validation of the close-range camera calibration model for narrow angles of view. (29th July 2015) - Percoco, Gianluca; Sánchez Salmerón, Antonio J
Abstract: The measurement of millimetre and micro-scale features is performed by high-cost systems based on technologies with narrow working ranges to accurately control the position of the sensors. Photogrammetry would lower the costs of 3D inspection of micro-features and would be applicable to the inspection of non-removable micro parts of large objects too. Unfortunately, the behaviour of photogrammetry is not known when photogrammetry is applied to micro-features. In this paper, the authors address these issues towards the application of digital close-range photogrammetry (DCRP) to the micro-scale, taking into account that in literature there are research papers stating that an angle of view (AOV) around 10° is the lower limit to the application of the traditional pinhole close-range calibration model (CRCM), which is the basis of DCRP. At first a general calibration procedure is introduced, with the aid of an open-source software library, to calibrate narrow AOV cameras with the CRCM. Subsequently the procedure is validated using a reflex camera with a 60 mm macro lens, equipped with extension tubes (20 and 32 mm) achieving magnification of up to 2 times approximately, to verify literature findings with experimental photogrammetric 3D measurements of millimetre-sized objects with micro-features. The limitation experienced by the laser printing technology, used to produce the bi-dimensional pattern on common paper, has been overcome using an accurate pattern manufactured with a photolithographic process. The results of the experimental activity prove that the CRCM is valid for AOVs down to 3.4° and that DCRP results are comparable with the results of existing and more expensive commercial techniques.